The Role of Need for Closure and Need for Cognition in Writing-Specific Psychological Factors. Issue 10 (26th November 2021) - Rezazadeh, Mohsen; Zarrinabadi, Nourollah
ABSTRACT: This study examined the role of need for closure and need for cognition in predicting second language (L2) writing-specific psychological factors, namely, self-efficacy, anxiety, motivation, and self-regulation. To do this, we collected self-report data from 186 undergraduate learners of English. Results of path analyses revealed that both need for closure and need for cognition predicted writing self-efficacy, anxiety, motivation, and self-regulation. In addition, mediation analyses showed that different aspects of need for closure predicted the psychological aspects of L2 writing indirectly through need for cognition. The findings highlight that learners' cognition and their tendency toward information processing and willingness to engage in effortful thinking play an essential role in their perception and emotions toward L2 writing. It is recommended that teachers pay particular attention to learners' need for cognition, need for closure, and the aforementioned writing-specific psychological factors in L2 writing classrooms.